"8A" framework for value stream selection – an empirical case study. Issue 5 (13th August 2018) - Narayanamurthy, Gopalakrishnan; Gurumurthy, Anand; Moser, Roger
Abstract : Purpose: Before initiating the implementation of change for transforming and improving an organization through lean thinking (LT), it has to first select a right value stream. Several implementation studies have been documented in literature, but not many studies have addressed this issue of value stream selection. The purpose of this paper is to propose and empirically validate a framework for selecting a value stream to implement LT. Design/methodology/approach: 8A framework is proposed by reviewing the literature on LT implementation case studies. Single case study methodology has been adopted to validate the application of 8A framework for selecting a value stream in an Indian educational institute. Since multiple qualifiers are considered simultaneously, a multi-criteria decision-making approach has been employed for choosing the value stream. Findings: Utility of the proposed 8A framework for value stream selection was confirmed through its successful application in an educational institute. Out of three alternatives in the case organization, the teaching alternative was chosen for further LT implementation based on the application of 8A framework. Qualitative cross-validation and sensitivity analysis also confirmed the robustness of the value stream selection made using the 8A framework. Research limitations/implications: Framework proposed in this study comprehensively captures the important qualifiers that were overlooked by the widely adopted first tenet of LT. Future research can attempt to generalize the applicability of 8A framework in different contexts including manufacturing, healthcare, software development, etc. A further study can be carried out in two similar case organizations or in two value streams of the same case organization (say in two different plants) to compare the differences in the outcome of lean implementation when one chooses its value stream for LT implementation without the application of the proposed framework, while another chooses it by applying the 8A framework. Practical implications: Through structured evaluation of the comprehensive set of qualifiers in 8A framework using a multi-criteria decision making model, an informed decision can be taken by the practitioners in selecting a value stream from the available alternatives before proceeding with the implementation of LT. Originality/value: After questioning the existing procedure of value stream selection for LT implementation, this study is the first to propose and validate an 8A framework that overcomes the limitations of the existing procedure. Study is also unique in the choice of the case organization as not many research papers have documented implementation of LT from the context of educational institutes.